Centralized base station sleep algorithm based on non-neighbor relation clustering in dense heterogeneous networks - Cao, Yikan; Xie, Zhibin; Wang, Yajun; Xia, Benqi (Dianxin Kexue, 2018)
A centralized base station sleeping algorithm based on non-neighbor relation clustering was proposed for dense heterogeneous networks. Firstly, based on the non-neighbor relationship criterion, the low power base stations with no direct switching relationship were clustered into several groups. Then, the low power base station running mode decision mechanism and possible base station sleeping decision mechanism was set according to the energy efficiency mean of base station in each cluster and the position relations between the users and the base station. At last, all clusters run the decision mechanism of inner cluster according to the order of the implementation of sleeping algorithm. The simulation results show that the proposed algorithm has satisfactory network performance.